PENINGKATAN KETERAMPILANMOTORIK KASAR SISWA MELALUI SENAM IRAMA DI KELAS I SD 1501 HURUNG JILOK - Nurhayati Siregar; Irma Sari Daulay; Netti Hasibuan (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Based on the results of the study it can be concluded that the improvement of students' gross motor skills through rhythmic gymnastics in class I SD Negeri 1501 Hurung Jilok obtained the percentage of completeness of gross motor skills of students in the complete category of 7 students or 30.43%, while the completeness of gross motor skills of students in the category of not yet complete 16 students or 69.57%, while the first cycle obtained the percentage of complete gross motor skills of students in the complete category of 13 students or 56.52%, while the complete gross motor skills of students in the incomplete category were 10 students or 43.48% and for cycle II it was obtained that the percentage of completeness of gross motor skills of students in the complete category was 21 students or 91.30%, while the completeness of gross motor skills of students in the incomplete category was 2 students or 8.70%. So it can be concluded that through rhythmic gymnastics that is applied it can improve the gross motor skills of students in class I SD Negeri 1501 Hurung Jilok.